PERLINDUNGAN HUKUM BAGI PASIEN PENGGUNA JAMKESMAS DALAM PELAYANAN KESEHATAN DI RSUD DR. RM. DJOELHAM BINJAI TERKAIT BERLAKUNYA BPJS DI BIDANG KESEHATAN - Elmas Dwi Ainsyiyah; Suhaidi Suhaidi; Utary Maharani Barus; Edy Ikhsan (Universitas Sumatera Utara, 2015)
ABSTRACT Health care service is closely related to the relationship of patients with health care supervisors (doctors) and health facility (hospital). Three problems of the research were as follows: how about the legal protection for Jamkesmas patients in the implementation of health care service in Indonesia related to the prevailing BPJS (Social Security Provider) in health, what factors which impeded the implementation of health service for Jamkesmas patients at RSUD (Regional General Hospital) Dr. RM Djoelham, Binjai, and how about the responsibility of the hospital management for the Jamkesmas patients at RSUD Dr. RM Djoelham, Binjai. Legal protection about the relationship among patients, doctors, and hospital is regulated in Law No. 29/2004 on , in Law No. 36/2009 , and in Law No. 44/2009 there is Law No. 40/2004 . The factors which impede the implementation of health care service for Jamkesmas patients are, among others, the examination is done by practicing doctors who have not passed the state licensing exams yet (interns). It is recommended that first, the hospital management should give legal protection for Jamkesmas patients by not discriminating them in providing health care services; secondly, the hospital management should give the compensation to the patients if the service is not satisfactory; and thirdly, patients should file a complaint to the hospital management as the health care service provider. Legal remedy which is used by Jamkesmas patients against the hospital management is by settling the dispute with prioritizing mutual agreement. Keywords: Health Care Service, Legal Protection, Jamkesmas